2015
DOI: 10.1186/s12889-015-2082-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neighbourhood walkability and daily steps in adults: a systematic review and meta-analysis

Abstract: BackgroundHigher street connectivity, land use mix and residential density (collectively referred to as neighbourhood walkability) have been linked to higher levels of walking. The objective of our study was to summarize the current body of knowledge on the association between neighbourhood walkability and biosensor-assessed daily steps in adults.MethodsWe conducted a systematic search of PubMed, SCOPUS, and Embase (Ovid) for articles published prior to May 2014 on the association between walkability (based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(100 citation statements)
references
References 52 publications
7
81
5
3
Order By: Relevance
“…The results showed that respondents who gave lower lack of cul-de-sac scores tended to indicate a PA of C3. Therefore, contrary to [21], this study found that a greater number of cul-de-sacs resulted in a PA of C3, possibly because every cul-de-sac in Nusantara has a small pedestrian lane to the other street, which increases the likelihood that respondents in Nusantara would walk easily around in their home vicinities but only within their residential district boundaries.…”
Section: Model 3 (Nusantara)contrasting
confidence: 84%
See 1 more Smart Citation
“…The results showed that respondents who gave lower lack of cul-de-sac scores tended to indicate a PA of C3. Therefore, contrary to [21], this study found that a greater number of cul-de-sacs resulted in a PA of C3, possibly because every cul-de-sac in Nusantara has a small pedestrian lane to the other street, which increases the likelihood that respondents in Nusantara would walk easily around in their home vicinities but only within their residential district boundaries.…”
Section: Model 3 (Nusantara)contrasting
confidence: 84%
“…Other studies have found that PNEO measures such as land use mix entropy [19][20][21], population density [19,21,22], traffic intersection density [13,[23][24][25][26] and proximity to recreation areas [26][27][28] influence the PA levels of older adults. While these types of PNEO measures are reliable in representing the objective physical characteristics of the neighbourhood environment that can strongly influence the PA level in older adults, in some cases, local considerations are also needed.…”
Section: Formulation Of Conceptual Modelmentioning
confidence: 96%
“…Street intersection density [60,61,62], land-use mix [63], population density [60], number of shops, distance to the closest Mass Transit Rail (MTR) station, and number of bus stops [64,65] were objectively assessed in the buffers of participants’ dwelling locations in GIS platform. The land-use mix was assessed by entropy score to show the degree of land use diversity of three types: Commercial, office, and residential [63].…”
Section: Methodsmentioning
confidence: 99%
“…Reviews assessing the relationship between the physical activity environment and individual physical activity behaviours have found walkability, more diverse land‐use mix, access to recreational facilities, public open space and green space, residential density, and street connectivity to be associated with higher physical activity levels in children and adolescents. In adults, neighbourhood walkability and opportunity for active transport were found to be associated with increased physical activity levels. A majority of studies in these reviews were cross‐sectional, and in one review, only a third of papers included objectively measured environments and physical activity levels.…”
Section: Introductionmentioning
confidence: 96%